Assessing the impact of climate change on mangrove crabs: the role of ontogenetic macrophysiology and settlement in the persistence of central and marginal populations - Mostert, Bruce Petrus (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
After a brief respite in the mid to late 20th century, macro physiology has come to the fore in elucidating large scale ecological patterns and processes as physiological assumptions often form the backbone of many predictive theories associated with species distributions. Critically, macro physiological patterns are valuable in explaining physiological variation across multiple scales and provide insights into the effects of climate change on populations spanning a wide range of latitudes. This can assist in predicting possible distribution expansions, contractions or shifts in light of current climate change scenarios. From this perspective, investigating intra- and inter-specific physiological responses to environmental stress may contribute to better understanding and predicting the effects of climate change on geographical ranges. Further, investigating the physiological effects to environmental stresses across ontogenetic stages allows for the identification of weak links within the lifecycle of a species. Additionally, determining settlement characteristics along a latitudinal cline provides integrated indications of the sustainability of populations, highlighting vulnerable regions in terms of repopulation of viable habitats. In this context, the present study aimed at establishing how temperature, in a physiological context, may affect reproductive biology of two species of mangrove crab, Perisesarma guttatum and Uca urvillei at the centre (Kenya) and edge (South Africa) of their distributional range along the east coast of Africa and highlight possible consequences for range distributions. A third species, Neosarmatium africanum, only in South Africa, was included to provide additional interspecies comparisons. Furthermore, settlement characteristics of brachyuran populations at the centre and edge of their distributional range were considered in order to determine how settlement may contribute to population persistence. Physiological investigations at the centre and edge of distributional range and across ontogenetic stages (larvae, stage 2 and 4 embryos, non-gravid and gravid females) under the concept of oxygen and capacity limitation of thermal tolerance (OCLTT), revealed that, for both species, populations at the centre of their distribution (Kenya) were generally more robust to increasing temperatures and generally displayed greater physiological stability with increasing temperatures compared to their conspecifics in South Africa. Variability in physiological robustness between regions, did however, differ among ontogenetic stages and species but, overall, were evident throughout. Within and between regions, adaptation to oxygen extraction in both milieus (air or water) was displayed for present temperature conditions but aerial respiration largely alleviated increased thermal stress due to overcoming the limitations of reduced oxygen availability and diffusiveness in water for all bimodal ontogenetic stages. Brooding eggs proved to be a physiologically critical process with either heighted oxygen consumption for gravid females or collapse of physiological processes demonstrated by supressed oxygen consumption. The physiological cost of brooding eggs, referred to as maternal costs, was reflected in in both Perisesarma guttatum and Uca urvillei where, in most cases, maternal costs were negative. Again, aerial respiration was able to alleviated increased thermal stress, as shown by positive maternal costs indicating sustained maternal care, but this mechanism was species and regionally specific. Settlement patterns differed between the edge and centre of distribution of the species studied. This difference was predominantly driven by zonal preference within the mangal and/or effects of new and full moon (lunar phase). Overall, settlement dynamics were more widely variable in South Africa, both spatially and temporally, than in Kenya. Finally, empirical physiological data from ontogenetic stages present during the reproductive process (early and late stage embryos) and from non-gravid and gravid females were used in conjunction with data mined from the existing literature to parameterise an individual based model designed to simulate reproductive output at the centre and edge of distribution of Perisesarma guttatum. Physiological data indicate that, in terms of reproductive output across increasing temperatures, populations based at the centre of their distribution presently outperform their counterparts at the edge of the species' distribution, but reproductive output stagnated as temperature rose. Edge of distribution populations consistently increased reproductive output with increasing temperatures to eventually outperform centre of distribution populations at higher simulated temperatures. Overall, results of the physiological and settlement studies suggest that with increased climate change there may be a contraction of distributional range of the study species from high latitudes to low latitudes, contrary to general poleward shifts/migrations seen in most species, with possible contractions of the entire ecosystem mirroring the disappearance of keystone mangrove macrofauna.
Keywords: Uncatalogued